PENDIDIKAN KARAKTER ANAK USIA DINI BERBASIS LINGKUNGAN ALAM (STUDI KASUS DI UNIVERSITAS MULAWARMAN) - Heryanto Heryanto (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2017)
The research aims to uncover (1) the meaning of the natural environment as a place to build character in early childhood; (2) learning activities that implement early childhood interactions with the natural environment; (3) the dimensions of the characters that formed in early childhood. The method used in this study is qualitative with historical approaach. Method sample is purposive and snowball sampling, while the sample size is determined based on the completeness of the information and data necessary. The study shows that the character education in the family-based nature will grow and develop awareness of self, others, and the environment as a place to his live, so behave courteously as a reflection of fundamental values.Keywords: early childhood, environment, nature, family.